Geospatial Technology for Effective Disaster Risk Reduction: Best practices in capacity building - S. P. Aggarwal; S. S. Kundu; K. K. Sarma (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences)
Geospatial technology, including remote sensing, Geographic Information Systems (GIS), and Global Navigation Satellite Systems (GNSS), is identified as a key component in disaster management. It enables hazard, risk, and vulnerability mapping, aiding in the development of effective evacuation plans and resource allocation strategies. Moreover, it facilitates the evaluation of the Sustainable Development Goals (SDGs) and can contribute to improving accountability. While geospatial technology has seen rapid development primarily in developed countries, there's a growing need to expand its adoption globally, particularly in developing and vulnerable regions. Capacity building initiatives are highlighted as crucial in achieving this goal, emphasizing the importance of education, training, and infrastructure development. India is a leading example in the application of geospatial technology for disaster risk reduction, with significant integration into various phases of disaster management. The government's commitment and leadership, along with extensive training programs facilitated by institutions like Indian Space Research Organization, have been instrumental in promoting the widespread use of geospatial technology. Furthermore, India's efforts extend beyond its borders, with capacity building initiatives targeted towards the Asia-Pacific region through the Centre for Space Science and Technology Education in Asia and the Pacific (CSSTEAP). These initiatives aim to equip officials with the necessary skills to apply geospatial technology in disaster management within their respective countries. The paper underscores the importance of integrating geospatial technology into DRR strategies to build resilient communities and minimize the impact of disasters. It emphasizes the need for concerted efforts in capacity building to meet the growing demand for skilled professionals and promote evidence-based decision-making in disaster management.